Pengaruh Motivasi Belajar, Peran Guru, dan Minat Belajar terhadap Hasil Belajar Siswa pada Mata Pelajaran Ekonomi SMA Negeri Webriamnata, Kec. Kewiku, Kabupaten Malaka - Seran, Enjel Ambrosiani; Data, Ari; Saragih, Fernando (Journal Economic Education, Business and Accounting, 2025)
One of the challenges faced in this research is the low student learning outcomes. This research aims to explore how learning motivation, the role of the teacher, and interest in learning can influence the learning outcomes of class XI students at Webriamata State High School. In this research, 147 students from class XI at the school were used as research subjects, which used a quantitative approach. Purposive sampling technique was applied to determine the sample, with a total of 88 respondents. Data collection was carried out through questionnaires and supporting documents. The data analysis method used includes linear multiple regression. The research results show that student learning outcomes in economics subjects are positively and significantly influenced by learning motivation (X1). Apart from that, the role of the teacher (X2) also has a significant positive impact on student learning outcomes. However, interest in learning (X3) does not show a significant influence on student learning outcomes in economics subjects. Overall, student learning outcomes in the field of economics are influenced simultaneously by learning motivation, the role of the teacher, and interest in learning.